Cost-aware process modeling in multiclouds. Issue 108 (September 2022) - Ritter, Daniel
Abstract: Process digitization and integration is an increasing need for enterprises. At the same time, process platform-as-a-service (PPaaS) vendors (e.g.,  business process- or integration-as-a-service) and their customers strive to minimize the cost of operation of platforms and processes. While current PPaaS technology mainly runs in single-clouds, multicloud settings are gaining importance. However, their promised freedom of selecting the best option for a specific problem is currently not realized. Moreover, important cloud-aspects like security constraints are handled in a cost-intensive manner for PPaaS vendors (e.g.,  by isolating tenants at container level). This leads to security vs. costs goal conflicts, while costs remain intransparent to process modelers. In this work, we propose a design-time placement method for processes in multiclouds that is cost-optimal for PPaaS problem sizes, and respects configurable security constraints of their customers. To make the solution tractable for larger, productive PPaaS processes deployments, it is relaxed by using a local search heuristic, and complemented by correctness-preserving model decomposition. This allows for a novel perspective on cost-aware process modeling from a process modeler's perspective. The multicloud process placement is evaluated on real-world integration processes with respect to cost- and runtime-efficiency, resulting in interesting trade-offs. The process modeler's perspective is investigated based on a new cost-aware modeling process, featuring the interaction between the user and the PPaaS vendor through ad-hoc multicloud cost calculation and correctness-preserving, process cost reduction proposals. Highlights: Cost-aware process modeling in multiclouds (platform perspective). Interaction between cloud process platform and their users (user perspective). Process modeling in multiclouds formalized as cost-efficient placement problem. Optimal solution of CEPP and practically applicable local search heuristic. Correctness checks for security-aware decomposition and improvements of processes. Prototype for case studies evaluating platform and user perspectives.